Nutrient Digestibility of Yankasa Rams Fed Brachiaria ruziziensis (Congo Grass) Hay with Different Supplements - I. Sani; A. Nuratu; S. S. Ahmad; A. Muhammed; S. H. Nuhu; A. Y. Girgiri; J.T. Amodu; R.J. Tanko; M. R. Hassan (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
This study was carried out to determine the nutrient digestibility of Brachiaria ruziziensis (Congo grass) hay by cannulated Yankasa rams fed different supplements. The research was carried out at Polycon Research farm, Federal Polytechnic Bauchi. Four (4) Yankasa rams, replicated three times were assigned to four dietary treatments of B. ruziziensis hay with different supplements for 21 days. Treatment diets were Treatment 1 (B. ruzizensis hay + wheat offal supplement), Treatment 2 (B. ruzizensis hay + maize offal supplement), Treatment 3 (B. ruzizensis hay + Groundnut haysupplement) and Treatment 4 (sole B. ruzizensis hay). Values for rumen liquor pH obtained showed that the experimental diets did not affect rumen pH across treatments at the various hours. The result indicated that the digestibility of dry matter was higher (P<0.05) for wheat offal (WO) 69.7% and lowest for B. ruziziensis (control) with 57.4%. Similarly, the crude protein and crude fibre digestibility followed the same trend as dry matter digestibility with WO having the highest values (P<0.05) which steadily declined to lowest levels in the control (B. ruziziensis). Similarly, the animals fed wheat offal supplement had best values (P<0.05) for nitrogen intake measured (12.5g/day) with the least value obtained in the control (B. ruziziensis) which was 6.3 g/day. Similarly, animals fed WO significantly (P<0.05) retained nitrogen (5.4g/day) than other treatment, with the least retention in the control animals (1.8g/day). Result indicated that animals fed B. ruziziensis + Wheat offal had best nutrient digestibility and nitrogen balance in the rams and hence recommended that B. ruziziensis hay should be supplemented with wheat offal at 355g/day.